Improving the output voltage quality in hybrid power plants using an integrated battery and supercapacitor system - Husniya I. Ibragimova; Kamoliddin Sh. Kadirov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: this article examines improving the quality and stability of electrical energy in solar-diesel hybrid power plants through the use of an integrated hybrid energy storage system based on batteries and supercapacitors. The main challenges of hybrid power plants include rapid fluctuations in inverter output voltage, dynamic load changes, variability in renewable energy sources (solar radiation), and harmonic distortion caused by nonlinear loads. These factors lead to increased total harmonic distortion (THD), phase errors, and RMS voltage instability. These factors lead to malfunctions in consumer equipment, reduced energy efficiency, and increased diesel generator over-runs. Aim: improving the quality of electrical energy supplied to the grid by reducing rapid voltage fluctuations, peak loads and harmonics (reducing the harmonic distortion coefficient, phase error and amplitude stability). Methods: international experience and methods of comparative analysis of demand management are used. Results: the combined use of batteries and supercapacitors in hybrid power plants offers significant benefits, including improved voltage stability, reduced harmonic distortion, extended battery life, and reduced diesel generator power consumption. This solution is highly effective for use in low-voltage grids, autonomous power supply for rural areas, industrial facilities, and Smart Grid systems..